Maize meal (posho) served at selected boarding schools in western Uganda is highly contaminated with aflatoxins - Oyesigye, E.; Nkurunungi, J.B.; Mlahagwa, W.; Raymond, A.; Mahuku, G.; Medina, A. (Walter de Gruyter GmbH, 2024)
The study aimed to evaluate food handling practices and assess the maize-bean supply chain in selected boarding schools of western Uganda. Additionally, it sought to determine the extent of aflatoxin exposure in the maize-bean meal consumed by students within the age range of 5 to 24. A cross-sectional study was conducted in two districts of Bushenyi and Sheema to gather 95 samples (31 beans, 32 maize flour, and 32 cooked maize flour-posho). In addition, 262 individual interviews were conducted. The findings revealed that only 9.38% of the schools store food as per World Health Organisation standards. The majority of schools (57.9%) purchase maize flour and beans from any stockist with no contractual obligations (random supplier), and all the 32 schools base on visual parameters, especially white colour, and smell to rule out aflatoxin contamination. Maize flour stored on the ground registered significantly (P = 0.0018) higher levels (54.3 ± 10.1 μg/kg) of total aflatoxins than that stored on a raised platform (14.7 ± 2.6 μg/kg). Likewise, the supplier significantly influenced total aflatoxins levels (P = 0.0064), with higher levels (44.6 ± 8.0 μg/kg) detected in maize flour supplied by a random supplier than a pre-qualified one (14.7 ± 2.6 μg/kg). Given the low levels (1.3 to 2.8 μg/kg), which are far less than the Maximum Tolerated Limit (MTL) of 10 μg/kg, aflatoxins do not pose a significant problem in beans. Aflatoxins exposure in younger children (5-12 years) was higher (61.5 ng/kg bw/day) than in older ones (13-24 years; 41.5 ng/kg bw/day). Similarly, the risk of developing hepatocellular carcinoma was greater in younger children (1.84 cases per 100,000 people) compared to older ones (1.24 cases per 100,000 people). The findings underscore an urgent need to formulate guidelines for procurement, storage, and food handling in schools, alongside intensifying inspection programmes for food handling. Additionally, there is need to expand the research scope by incorporating a greater number of schools from varied geographical areas within Uganda, while rigorously monitoring the entirety of the food supply chain.